Metabolic sculpting of the mitochondria, cell signaling and the cancer phenotype - Sharpe, Martyn A.; Ismail, Nyla; Baskin, David S. (Translational Cancer Research; Vol 6, Supplement 1 (February 28, 2017): Translational Cancer Research, 2017)
An understanding of metabolic pathways, most notably abnormal metabolite states that agitate normal physiology, is fundamental to the approach to all disease oriented research and can have broad impact on our understanding of cancer treatment. Recent research implicates mitochondrial metabolism in the induction of widespread changes in macrophage gene expression and alterations in the anti/pro-inflammatory cytokine generation. We examine the role of metabolic gene signaling in the recent work of Mills et al., in the framework of the cancer phenotype. A shift in the rate of mitochondrial succinate oxidation modifies the steady state levels of superoxide/hydrogen peroxide, which in turn modulates the levels of active hypoxia inducible factor 1 alpha subunit (HIF-1α), and can result in ‘chemical hypoxia’. Chemical hypoxia occurs when the hypoxia signaling pathways are active, at non-hypoxic oxygen levels. In this paper, we examine the work of Mills et al., and provide data for gliomas that further supports the hypothesis that an altered metabolism changes in the tumor microenvironment. This alteration can distinctly drive the cell to a set of interconnected molecular pathways, with both 2-oxoglutarate and succinate levels acting as regulators.